Kyoto protocol and social accounting implication on global-warming in Malaysia: An action research approach - Lee, M.Y.; Susela, D.; Wong, E.S.K. (Academic Journals, 2011)
This study examines the relationship between social change demands and tactical decision making processes resulting from apparent global-warming and climate-change by employing an action research methodology. The objective was to uncover the perceptions of Malaysian corporate management concerning the present debate on climate change. These corporate officers occupy the top decision making positions that disperse the day to day operational decisions as well as being directly involved with longer term considerations, particularly of the financial implications of the debates and forthcoming national and international legal implications concerning global-warming/climate-change. This research is a descriptive study. Interviews with the management of 30 randomly selected companies were conducted, and the results and conclusions support the view that carbon trading is not an effective approach to resolve the apparent carbon dioxide problem. This study has provided greater understanding of the corporate view regarding measures aimed at prevention of large rise in global temperatures.